2020
DOI: 10.3389/fped.2020.546544
|View full text |Cite
|
Sign up to set email alerts
|

Association of Protein and Vitamin D Intake With Biochemical Markers in Premature Osteopenic Infants: A Case-Control Study

Abstract: Osteopenia in preterm infants (OP) remains an important challenge and is largely dependent on nutritional post-natal intake of factors influencing bone mineralization. We conducted a prospective case-control study to evaluate the importance of protein and vitamin D intake in OP among neonates with birth weight <1,250 g. Simultaneous serum parathyroid hormone (PTH), alkaline phosphatase (ALP), calcium (Ca), phosphorus (P), vitamin D and protein levels were measured during the first six post-natal weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 48 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…Bone mineral density greater than 0.068 g/ cm 2 has been reported to be associated with a low risk of developing MBDP. However, DEXA imaging is complicated by limited availability, cost, and infant movement during the test, distorting the results [16,17].…”
Section: Early Screening: Radiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Bone mineral density greater than 0.068 g/ cm 2 has been reported to be associated with a low risk of developing MBDP. However, DEXA imaging is complicated by limited availability, cost, and infant movement during the test, distorting the results [16,17].…”
Section: Early Screening: Radiologymentioning
confidence: 99%
“…necrotizing enterocolitis, bronchopulmonary dysplasia (BPD)] found in preterm infants [16]. Studies utilizing DEXA scans for evaluation of bone mineral content show that at 6 months of age, bone mineral content is often lower in preterm infants than in term infants and associated with poor postnatal growth from MBDP [16,17]. Xie et al showed that infants born at less than 29 weeks gestational age at birth were shorter and lighter than those born fullterm had lower bone mineral density (BMD) at the femoral neck in young adulthood (18-29 years of age).…”
Section: Long-term Consequencesmentioning
confidence: 99%
See 3 more Smart Citations